Modification of the saturation magnetization of exchange bias thin film systems upon light-ion bombardment. (8th February 2017) - Huckfeldt, Henning; Gaul, Alexander; David Müglich, Nicolas; Holzinger, Dennis; Nissen, Dennis; Albrecht, Manfred; Emmrich, Daniel; Beyer, André; Gölzhäuser, Armin; Ehresmann, Arno
Abstract: The magnetic modification of exchange bias materials by 'ion bombardment induced magnetic patterning' has been established more than a decade ago. To understand these experimental findings several theoretical models were introduced. Few investigations, however, did focus on magnetic property modifications caused by effects of ion bombardment in the ferromagnetic layer. In the present study, the structural changes occurring under ion bombardment were investigated by Monte-Carlo simulations and in experiments. A strong reduction of the saturation magnetization scaling linearly with increasing ion doses is observed and our findings suggest that it is correlated to the swelling of the layer material based on helium implantation and vacancy creation.